Analysis Of Critical Success Factors In Penetration Testing Delivery Projects At Pt. Abcd Using A Fuzzy Delphi Method - Zulfirman Zulfirman; Ruri Agung Wahyuono (Eduvest - Journal of Universal Studies, 2026)
The success of penetration testing project delivery is influenced not only by technical factors but also by an organization’s ability to manage critical operational and managerial elements in an integrated manner. In the case of PT. ABCD, recurring challenges such as dynamic scope changes and suboptimal resource coordination highlight the absence of a validated Critical Success Factors (CSFs) framework. Therefore, this study aims to identify, validate, and prioritize the key determinants that contribute to successful penetration testing project delivery. The research began with a comprehensive synthesis of multidisciplinary literature from project management, information technology, agile practices, and cybersecurity domains, which was then combined with internal organizational lessons learned. This hybrid approach produced 11 preliminary CSF candidates. To ensure the robustness of the research instrument, classical statistical tests were applied, namely Pearson Product Moment validity testing and Cronbach’s Alpha reliability analysis, which confirmed the consistency and adequacy of the measurement tool. Subsequently, the CSF candidates were evaluated by 21 experts representing Project Management Office, Sales & Business, and Technical/Pentester functions. The Fuzzy Delphi Method was employed to accommodate uncertainty in expert judgment, utilizing triangular fuzzy numbers, expert agreement levels, threshold distance (d) for consensus measurement, and alpha-cut defuzzification for final selection. The results indicate that 10 of the 11 CSFs achieved strong consensus, meeting the criteria of EA ≥ 75%, d ≤ 0.2, and alpha-cut ≥ 0.75. The final prioritization shows that communication effectiveness, stakeholder coordination, technical team readiness, and adaptive management are the most influential success factors.